Emollients with natural emulsifier Olivem 1000 as topical formulations for urea or sodium hyaluronate - Magdalena Wróblewska; Katarzyna Winnicka (Polskie Towarzystwo Farmaceutyczne, 2024)
Xerosis is one of the common dermatological problems. Preparations recommended for daily care of the dry skin are emollients. Emollient preparations demonstrate a moisturizing effect, they soften and smoothen the skin, keep water in the epidermis, supplement lipids of skin upper layers and protect from external harmful agents. The purpose of this study was to develop and characterize emollients containing natural emulsifier Olivem 1000 as topical delivery systems for urea or sodium hialuronate. Physicochemical and mechanical properties of designed formulations were evaluated. Moreover, ex vivo adhesion study on the hairless mice skin as a model of adhesive layer was carried out and in vivo preliminary assessment of transepidermal water loss (TEWL) was performed. Prepared emollient formulations were characterized by smooth consistency, they were easily spreadable on the skin surface and showed no phase separation. Formulations containing xanthan gum as a thickening agent were characterized by higher viscosity, hardness, cohesiveness and adhesiveness values. Prepared emollients showed thixotropic properties and they were classified as non-Newtonian shear thinning systems. All prepared emollients demonstrated bioadhesive properties. The analysis of TEWL showed that the greatest decrease in the TEWL value was noted in the case of emollient containing sodium hyaluronate which was applied to the person with the skin described as "the skin in a very poor condition". The results of the conducted research indicate that developed emollients containing natural emulsifier Olivem 1000 seem to be a promising form of care preparations for topical use in case of chronic dryness of the skin.